Thermal and non-thermal effects of capacitive–resistive electric transfer application on different structures of the knee: a cadaveric study - Jacobo Rodríguez-Sanz (Nature Portfolio, 2020)
Abstract Capacitive–resistive electric transfer therapy is used in physical rehabilitation and sports medicine to treat muscle, bone, ligament and tendon injuries. The purpose is to analyze the temperature change and transmission of electric current in superficial and deep knee tissues when applying different protocols of capacitive–resistive electric transfer therapy. Five fresh frozen cadavers (10 legs) were included in this study. Four interventions (high/low power) were performed for 5 min by a physiotherapist with experience. Dynamic movements were performed to the posterior region of the knee. Capsular, intra-articular and superficial temperature were recorded at 1-min intervals and 5 min after the treatment, using thermocouples placed with ultrasound guidance. The low-power protocols had only slight capsular and intra-capsular thermal effects, but electric current flow was observed. The high-power protocols achieved a greater increase in capsular and intra-articular temperature and a greater current flow than the low-power protocols. The information obtained in this in vitro study could serve as basic science data to hypothesize capsular and intra-articular knee recovery in living subjects. The current flow without increasing the temperature in inflammatory processes and increasing the temperature of the tissues in chronic processes with capacitive–resistive electric transfer therapy could be useful for real patients.